Hydrothermal Synthesis of Flower-Like α-Quartz Nanostructures from Iran Kaolin - Sahar Pirkhedri; Mansoor Anbia; Rahmatollah Rahimi; Farideh Bandarchian (Iranian Journal of Chemistry & Chemical Engineering, 2016)
Over the past many years, synthesized silica (SiO2) has attracted wide attention because of its unique characteristics, such as low density, low thermal conductivity, high surface area, high thermal shock resistance and high specific strength. In this study, Flower-like α-quartz nano-structures have been synthesized through the hydrothermal method. The synthetic α-quartz powder was obtained using the feedstock of locally kaolin after 15 h. reaction at 180°C. The characterization of the product was investigated using X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier Transform InfraRed (FT-IR) spectrometer. The FT-IR spectrum of the nano-crystalline powders confirms the presence of silica. SEM studies have revealed flower-like structures consisting of nano-sheets. In the synthetic quartz, most of the population is of nano-sized and lies between 1 µm to 15 µm. This developed method has many advantages such as synthesis at low temperature and desired pH to yield superior product of desired specification.